Pekan Ngaji dan Peningkatan Motivasi Belajar Siswa Kelas X MA C Mambaul Ulum Bata-Bata - Ridho, Ali (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2019)
The Research of An International event Pekan Ngaji and the Increasing of Learning Motivation of Students in Class 10- of MA C Senior High school of Mambaul Ulum Bata-Bata was conducted to find out the role of the Pekan Ngaji which became the annual agenda of Bata-Bata Islamic Boarding School contributing to the improvement of learning motivation of class X MA students. C, a class that directly enjoys this program because it will become the object of guidance (Learning) as a participant. This research is a type of qualitative research. The approach that we will use is the Phenomenological Approach with a descriptive approach that describes the learning motivation of class 10 MA C. Senior High School of Mambaul Ulum Bata-Bata. The research that we will conduct is used a number of methods in collecting datas, namely: observation, interviews, and document studies. After the data is obtained, it will be analyzed by descriptive-analytical data analysis method. From this study it was found that the motivation of stidents in class X MA C is rapidly increasing. Based on the analysis of the researcher, their motivation is biogenetic or motives derived from the needs of the organism for the sake of their survival, sociogenetic and theological motives. The most visible indication of them is their participation in extracurriculer programs in Islamic boarding schools which held by a particular institution namely autonomous bodies.